PENGGUNAAN WHATSAPP SEBAGAI MEDIA KOMUNIKASI INTERPERSONAL PADA MAHASISWA PERANTAUAN DI KOTA BATAM - Putri, Yeyen Rahma; Syafi'i, Muhammad (SCIENTIA JOURNAL, 2020)
Technological developments today have profoundly influenced aspects of human life, and communication is no exception. Whatsapp is one of the most widely used applications by society especially among college students. The study aims to find out how interpersonal communication and social interaction are using the whatsapp as an interpersonal communication media on the family of visiting students in the city of batam. The research used in this study is qualitative methods, the acquisition of these studies USES observation of interviews, and documentation. The Whatsapp server to convey information and as a medium a long-distance communication link using communication interpersonal in the riau islands university student ward. App for an interpersonal communication media on the oiling students in batam city is the interpersonal communication children have with their parents has differences, some who regularly communicate and some who only do communications once a week. Interpersonal communication is strongly influenced by social interactions in an attitude of openness, empathy, supportive behavior, and positive behavior as a form of interpersonal communication between children and parents. It is also one way to overcome communication barriers to interpersonal communication. Keywords: family, interpersonal communication, social interaction, whatsapp